Perovskite solar cell, preparation method thereof and perovskite photovoltaic module comprising perovskite solar cell
By introducing a functional group interface encapsulation layer with anchoring effect in the perovskite photovoltaic module, the problem of insufficient stability of perovskite materials is solved, and the stability and safety of the module are significantly improved.
Patent Information
- Application Number
- CN202411753545.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The intrinsic stability of perovskite materials in perovskite photovoltaic modules leads to internal ion migration and lead leakage problems, affecting the stability and safety of the module.
An interface encapsulation material with excellent barrier properties is introduced, including functional groups that can form an anchoring effect with the metal electrode, such as thiol groups, phosphine groups, amine groups, etc., to form an interface encapsulation layer to block ion migration in the perovskite film and leakage of lead ions.
Significantly inhibit ion migration in perovskite film, prevent lead leakage, and improve the stability and safety of perovskite photovoltaic modules.
Smart Images

Figure CN119653972A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and relates to a perovskite solar cell and a preparation method thereof, and a perovskite photovoltaic module comprising the same. Background Art
[0002] Perovskite solar cells are a new type of thin-film photovoltaic technology that has attracted much attention in recent years. Their advantages such as high power conversion efficiency, low cost and low-temperature printing make them a research hotspot for the current photovoltaic industry and university research and development teams. With the rapid development of research fields such as nanotechnology and materials science, the semiconductor characteristics and physical and chemical properties of perovskite materials have gradually been deeply revealed, which provides a theoretical basis and technical support for the development of perovskite photovoltaic technology. However, the commercialization process of perovskite photovoltaic modules still faces a huge obstacle of insufficient working stability. This problem mainly stems from two aspects. The first is internal factors, which are reflected in the lattice degradation reaction caused by ion migration in the perovskite component: in actual use, the organic cations (CH 3 NH 3 + 、CH(NH 2 ) 2+ )) and halogen ions (I - ) and other components are prone to spontaneous ion migration, which leads to their decomposition to produce hydrogen iodide (HI) and iodine (I 2 ), these decomposition products will further react with common metal electrode materials (such as aluminum (Al), silver (Ag), copper (Cu), etc.) to form AlI 3 、AgI、CuI 2 Compounds such as iodine and iodine. In the various aging processes of batteries, according to the principle of chemical equilibrium, the presence of corresponding by-products will accelerate the layer-by-layer degradation of perovskite crystals, directly leading to a permanent decrease in battery efficiency. The second is external factors, mainly including extreme atmospheres such as humidity, oxygen, temperature and light that the battery may be exposed to under working conditions: First, the erosion of perovskite photovoltaic modules by moisture will trigger the hydrolysis process of the perovskite film, causing it to decompose and degrade in performance. The impact mechanism is shown in the following reaction equations ① and ②; secondly, oxygen can accelerate the oxidative decomposition of perovskite materials, especially when the temperature is high or in a strong light environment, the presence of oxygen will aggravate the degradation rate of the perovskite layer, and the specific impact process is shown in the following reaction equations ③ and ④; finally, temperature fluctuations, whether the temperature rises or falls, may affect the crystallization quality and stability of the perovskite material, thereby having a negative impact on the photoelectric conversion efficiency of the battery.
[0003]
[0004] O 2 +e - =O2 - ③
[0005] 4CH 3 NH 3 PbI 3 +O 2 - →4PbI 2 +2I 2 +2H 2 O+4CH 3 NH 2 ④
[0006] Therefore, in order to meet the working stability standards required for commercial certification, it is necessary to carry out reasonable packaging design for perovskite photovoltaic modules. In this regard, we can learn from the more mature crystalline silicon photovoltaic module packaging process based on the barrier interface design of perovskite materials. In crystalline silicon solar cells, the cells are usually connected to the backplane and glass through hot melt adhesive film, which can not only isolate water and oxygen, but also provide rigid support. The service life of the packaged components can reach more than 25 years.
[0007] The existing component packaging technology generally adopts the following steps: First, select suitable packaging materials, including cover materials (polyethylene terephthalate composite film (PET), polyimide composite film (PI), flexible glass polyvinyl butyral film (PVB), etc.), edge sealant (butyl glue, epoxy resin, polyurethane glue, polybutadiene oligomer, acrylic resin glue, etc.), and inner adhesive (polyolefin adhesive film (POE), acrylic resin glue, epoxy resin glue, polyurethane glue, etc.). Then use an appropriate size of inner adhesive to cover the top of the battery, and use edge sealant on the edge of the battery to ensure that the active area of the battery is isolated from the external environment. Finally, use an appropriate process (such as hot pressing, ultraviolet (UV) curing, etc.) to firmly fix the cover material on the battery to ensure that the bonding strength between the cover material and the battery is sufficient to ensure the integrity and stability of the package. This packaging method is widely used in the packaging of various components. However, this method can only isolate the influence of the external environment on the perovskite photovoltaic module, and the internal factors affecting the stability of the perovskite photovoltaic module have not been resolved.
[0008] Therefore, in the art, it is desired to develop a perovskite solar cell that can solve the problem of insufficient intrinsic stability of perovskite materials in perovskite photovoltaic modules. Summary of the invention
[0009] In view of the shortcomings of the prior art, the object of the present invention is to provide a perovskite solar cell and a preparation method thereof and a perovskite photovoltaic module containing the same. The present invention provides a perovskite solar cell that optimizes the wet-heat stability and lead leakage of the perovskite photovoltaic module. By introducing an interface encapsulation material with excellent barrier properties, the ion migration in the perovskite film can be significantly inhibited, and the leakage of lead ions can be effectively curbed, thereby improving the safety and stability of the perovskite photovoltaic module.
[0010] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides a perovskite solar cell, the perovskite solar cell comprising a conductive substrate, a perovskite layer, an interface encapsulation layer and a metal electrode layer, wherein the interface encapsulation layer is disposed adjacent to the metal electrode layer;
[0012] The material of the interface encapsulation layer contains functional groups that can form an anchoring effect with the metal electrode, including thiol groups (-SH), phosphine groups (-PR 2 ), amine (-NH 2 ), amide group (-CONH 2 ) or cyano (-CN) or a combination of at least two of them. These functional groups have atoms that can provide lone pairs of electrons or have strong electronegativity, thereby forming coordination bonds or similar chemical bonds with the metal center.
[0013] In the perovskite solar cell provided by the present invention, the material of the interface encapsulation layer contains a functional group that can form an anchoring effect with a metal electrode (such as Ag, etc.), and the material of the interface encapsulation layer can also form an anchoring effect with lead ions (Pb 2+ ) can effectively block the migration of iodine ions and metal electrodes to avoid their direct contact and reaction, and also prevent lead (Pb) from leaking into the external environment, thereby significantly improving the stability and safety of perovskite photovoltaic modules.
[0014] Studies have shown that the factors affecting the internal stability of perovskite photovoltaic modules are mainly the iodine ions (I - ) and Ag migration, under normal circumstances, this is a reversible ion migration process. However, once the migrated ions (I -) reacts with the metal electrode, this reversible process will be broken, resulting in irreversible layer-by-layer degradation of the perovskite film, and at the same time, reverse corrosion of the metal electrode. The present invention can effectively reduce ion migration inside the perovskite and inhibit lead leakage by introducing an interface encapsulation layer containing functional groups that can form an anchoring effect with the metal electrode. The interface encapsulation layer material is tightly combined with the top metal electrode, which can weaken the direct reaction between the metal electrode and the iodine ions in the perovskite, and significantly improve the safety and stability of the perovskite photovoltaic module.
[0015] Preferably, the material of the interface encapsulation layer includes any one of 2-mercaptoethanol, tricyclohexylphosphine, triphenylphosphine, dithiothreitol, ethanethiol, ethylenediamine, triethylamine, bis(dibenzylideneacetone)diiminenickel bis(triphenylphosphine), triisopropylphosphine, pentafluorophenyl diphenyl phosphate, tributylphosphine, tricyanomethane, and dicyanomethane, or a combination of at least two thereof.
[0016] Preferably, the thickness of the interface encapsulation layer is 10-20 nm, for example, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, 20 nm, etc.
[0017] Preferably, the perovskite solar cell further comprises any one of a hole transport layer, an electron transport layer, and a buffer layer, or a combination of at least two of them.
[0018] Preferably, the perovskite solar cell comprises a conductive substrate, a hole transport layer, a perovskite layer, an electron transport layer, a buffer layer, an interface encapsulation layer, and a metal electrode layer which are stacked in sequence.
[0019] Preferably, the conductive substrate comprises indium tin oxide (ITO) conductive film polyethylene naphthalate (PEN).
[0020] Preferably, the material of the metal electrode layer includes any one of aluminum, silver and copper.
[0021] It should be noted that the present invention does not specifically limit the materials of the hole transport layer, the perovskite layer, the electron transport layer, and the buffer layer, which can be materials conventionally used in the prior art. For example, the material of the hole transport layer can be [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (MEO-4PACZ) and / or (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid (MEO-2PACZ); the perovskite layer can be prepared using methyl bromide, iodomethane, methyl chloride, cesium iodide, lead iodide, lead bromide, etc. as raw materials, and a mixture of sulfone solvents and amide solvents as solvents; the material of the electron transport layer can be C60, etc.; the material of the buffer layer can be 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP), etc.
[0022] Preferably, the thickness of the hole transport layer is 20-100 nm, for example, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.
[0023] Preferably, the thickness of the perovskite layer is 300-700 nm, for example, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, etc.
[0024] Preferably, the thickness of the electron transport layer is 20-100 nm, for example, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, etc.
[0025] Preferably, the buffer layer has a thickness of 5-50 nm, for example, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, etc.
[0026] In a second aspect, the present invention provides a method for preparing a perovskite solar cell as described in the first aspect, the preparation method comprising the following steps:
[0027] (1) providing a conductive substrate;
[0028] (2) forming a hole transport layer on the conductive substrate;
[0029] (3) forming a perovskite layer on the hole transport layer;
[0030] (4) forming an electron transport layer on the perovskite layer;
[0031] (5) forming a buffer layer on the electron transport layer;
[0032] (6) mixing the material of the interface encapsulation layer and the solvent, stirring to obtain an interface encapsulation layer precursor solution, and coating the interface encapsulation layer precursor solution on the buffer layer by a slit coating method to form an interface encapsulation layer;
[0033] (7) Forming a metal electrode layer on the interface encapsulation layer to obtain the perovskite solar cell.
[0034] Preferably, the solvent in step (6) comprises any one of 2,2,2-trifluoroethanol, tetrahydrofuran, and 2,2,2-trifluoroethyl methyl ether, or a combination of at least two thereof.
[0035] Preferably, in step (6), based on 1 mL of the solvent, the amount of the material of the interface encapsulation layer is 0.5-2 mg, for example, 0.5 mg, 0.6 mg, 0.8 mg, 1 mg, 1.2 mg, 1.4 mg, 1.6 mg, 1.8 mg, 2 mg, etc.
[0036] Preferably, the solution is kept at room temperature during the stirring process in step (6).
[0037] Preferably, the stirring in step (6) is stirring until the material of the interface encapsulation layer is completely dissolved.
[0038] Preferably, during the slit coating process in step (6), the gap between the slit coating head and the substrate is controlled to be 50-100 μm, for example, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, etc., and the speed is 8-12 mm / s, for example, 8 mm / s, 8.5 mm / s, 9 mm / s, 9.5 mm / s, 10 mm / s, 10.5 mm / s, 11 mm / s, 11.5 mm / s, 12 mm / s, etc.
[0039] For the method for preparing a perovskite solar cell provided by the present invention, the present invention does not specifically limit the preparation raw materials, specific steps and parameters involved in steps (1) to (5) and step (7), and the preparation can be carried out with reference to conventional steps in the prior art. Exemplarily, the method for preparing a perovskite solar cell according to the present invention comprises the following steps:
[0040] (1) Tear off the protective films on both sides of the ITO conductive film PEN, put it into a laser etcher for etching, and set aside.
[0041] (2) Immersing the ITO conductive film PEN substrate obtained in step (1) into a SAM solution to prepare a hole transport layer with a thickness of 20-100 nm (e.g., 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.), wherein the SAM solution is a mixed solution of MEO-4PACZ or MEO-2PACZ and ethanol.
[0042] (3) Taking the mass and definition of the drugs methylamine bromide, iodomethane, methylamine chloride, cesium iodide, lead iodide, and lead bromide as 100%, methylamine bromide is 0.1% to 2% (e.g., 0.1%, 0.3%, 0.5%, 1%, 1.5%, 2%, etc.), iodomethane is 10% to 30% (e.g., 10%, 15%, 20%, 25%, 30%, etc.), methylamine chloride is 0.5% to 5% (e.g., 0.5%, 1%, 1.5%, 2%, 2.5%, etc.), 5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.), lead iodide is 50% to 80% (for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc.), lead bromide is 1% to 5% (for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.), and cesium iodide is the balance; the solvent is a first solvent (dimethyl sulfoxide or N-methylpyrrolidone) and a second solvent ( The second solvent is 70% to 90% (e.g., 70%, 75%, 80%, 85%, 90%, etc.) by volume, and the first solvent is 10% to 30% (e.g., 10%, 15%, 20%, 25%, 30%, etc.), and the above-mentioned drugs and solvents are mixed and stirred at 60-80°C (e.g., 60°C, 65°C, 70°C, 75°C, 80°C, etc.). The perovskite precursor solution is prepared after 10-15 hours (for example, 10 hours, 12 hours, 14 hours, 15 hours, etc.) for use, and the perovskite precursor solution is slit-coated on the surface of the hole transport layer obtained in step (2) to prepare a perovskite layer with a thickness of 300-700nm (for example, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, etc.).
[0043] (4) C60 is evaporated on the surface of the perovskite layer obtained in step (3) to prepare an electron transport layer with a thickness of 20-100 nm (for example, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, etc.), and then placed in a laser etcher for etching.
[0044] (5) BCP is evaporated on the surface of the C60 obtained in step (4) to prepare a buffer layer with a thickness of 5-50 nm (e.g., 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, etc.).
[0045] (6) Add the interface encapsulation layer material into the solvent and stir, and keep the solution at room temperature during the stirring process. The prepared solution is stirred at room temperature for 20-30 hours (e.g., 20 hours, 22 hours, 24 hours, 26 hours, 28 hours, 30 hours, etc.) to obtain an interface encapsulation layer precursor solution that can be used for slit coating. The interface encapsulation layer is prepared on the surface of the BCP buffer layer obtained in step (5) by slit coating. The gap between the slit coating head and the substrate is fixed at 50-100 μm (e.g., 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, etc.), and the speed is fixed at 8-12 mm / s (e.g., 8 mm / s, 8.5 mm / s, 9 mm / s, 9.5 mm / s, 10 mm / s, 10.5 mm / s, 11 mm / s, 11.5 mm / s, 12 mm / s, etc.) for printing preparation.
[0046] (7) A metal electrode is evaporated on the surface of the interface encapsulation layer obtained in step (6), and the layer is placed in a laser etcher for etching.
[0047] In a third aspect, the present invention provides a perovskite photovoltaic module, wherein the perovskite photovoltaic module comprises the perovskite solar cell as described in the first aspect.
[0048] Preferably, the perovskite photovoltaic module is a flexible module with an area of 100 cm 2 .
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] The perovskite solar cell provided by the present invention comprises an interface encapsulation layer, wherein the material of the interface encapsulation layer comprises a functional group that can form an anchoring effect with a metal electrode (such as Ag, etc.), and the material of the interface encapsulation layer can also form an anchoring effect with lead ions (Pb 2+ ) can effectively block the migration of iodine ions and metal electrodes to avoid their direct contact and reaction, and also prevent lead (Pb) from leaking into the external environment, thereby significantly improving the stability and safety of perovskite photovoltaic modules. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 A schematic diagram of the structure of a perovskite solar cell provided in Example 1;
[0052] Among them, 1-ITO conductive film PEN, 2-hole transport layer, 3-perovskite layer, 4-electron transport layer, 5-buffer layer, 6-interface encapsulation layer, 7-metal electrode layer.
[0053] Figure 2This is a comparison chart of the normalized absorption intensity test results of the perovskite solar cell provided in Example 1 and Comparative Example 1.
[0054] Figure 3 This is a curve showing the change of lead concentration in water over time after the perovskite solar cells provided in Example 1 and Comparative Example 1 are placed in water.
[0055] Figure 4 This is a graph showing the change in the photoelectric conversion efficiency ratio of the perovskite solar cell provided in Example 1 and Comparative Example 1 over time in an air environment with a relative humidity of 50%. DETAILED DESCRIPTION
[0056] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0057] Example 1
[0058] In this embodiment, a perovskite solar cell is provided, and its structural schematic diagram is as follows Figure 1 As shown, the perovskite solar cell includes a conductive substrate (ITO conductive film PEN) 1, a hole transport layer 2, a perovskite layer 3, an electron transport layer 4, a buffer layer 5, an interface encapsulation layer 6, and a metal electrode layer 7 which are stacked in sequence.
[0059] The preparation method comprises the following steps:
[0060] (1) Tear off the protective films on both sides of the ITO conductive film PEN, put it into a laser etcher for etching, and set aside.
[0061] (2) The ITO conductive film PEN substrate obtained in step (1) is immersed in a SAM solution to prepare a hole transport layer with a thickness of 50 nm. The SAM solution is a mixed solution of MEO-4PACZ and ethanol (wherein the concentration of MEO-4PACZ in the mixed solution is 0.5 mmol / L).
[0062] (3) The mass and definition of the drugs methyl bromide, iodoformamidine, methyl chloride, cesium iodide, lead iodide, and lead bromide are 100%, wherein methyl bromide is 1%, iodoformamidine is 20%, methyl chloride is 3%, lead iodide is 65%, lead bromide is 3%, and cesium iodide is the balance; the solvent is a mixture of a first solvent (dimethyl sulfoxide) and a second solvent (amide solvent, N,N-dimethylformamide), wherein the second solvent is 80% and the first solvent is 20% by volume, the above drugs are mixed with the solvent and stirred at 70° C. for 12 hours to prepare a perovskite precursor solution for use (wherein, the concentration of the drugs in the perovskite precursor solution is 1.1 mol / L), and the perovskite precursor solution is slit-coated on the surface of the hole transport layer obtained in step (2) to prepare a perovskite layer having a thickness of 500 nm.
[0063] (4) C60 is evaporated on the surface of the perovskite layer obtained in step (3) to prepare an electron transport layer with a thickness of 30 nm, and the layer is placed in a laser etcher for etching.
[0064] (5) BCP is evaporated on the surface of the C60 obtained in step (4) to prepare a buffer layer with a thickness of 10 nm.
[0065] (6) Add 1 mg of the interface encapsulation layer material (2-mercaptoethanol) to 1 mL of the solvent (2,2,2-trifluoroethanol) and stir, keeping the solution at room temperature during the stirring process. Continue stirring the prepared solution at room temperature for 24 hours to obtain an interface encapsulation layer precursor solution that can be used for slit coating. The interface encapsulation layer is prepared on the surface of the BCP buffer layer obtained in step (5) by slit coating. The gap between the slit coating head and the substrate is fixed at 80 μm, and the speed is fixed at 10 mm / s for printing. The thickness of the prepared interface encapsulation layer is 15 nm.
[0066] (7) A metal electrode (Ag) is evaporated on the surface of the interface encapsulation layer obtained in step (6) to obtain a metal electrode layer with a thickness of 100 nm, which is then placed in a laser etcher for etching.
[0067] Example 2
[0068] The only difference between this embodiment and embodiment 1 is that in step (6), the interface encapsulation layer material (2-mercaptoethanol) is replaced with an equal mass of tricyclohexylphosphine.
[0069] Example 3
[0070] The only difference between this embodiment and embodiment 1 is that in step (6), the interface encapsulation layer material (2-mercaptoethanol) is replaced with an equal mass of tributylphosphine.
[0071] Example 4
[0072] The only difference between this embodiment and embodiment 1 is that in step (6), the amount of the interface encapsulation layer material (2-mercaptoethanol) used is 0.5 mg, and the thickness of the prepared interface encapsulation layer is 10 nm.
[0073] Example 5
[0074] The only difference between this embodiment and embodiment 1 is that in step (6), the amount of the interface encapsulation layer material (2-mercaptoethanol) is 2 mg, and the thickness of the prepared interface encapsulation layer is 20 nm.
[0075] Comparative Example 1
[0076] The only difference between this comparative example and Example 1 is that the provided perovskite solar cell does not include an interface encapsulation layer, and accordingly, the preparation method does not include step (6), in which a metal electrode is evaporated on the buffer layer to form a metal electrode layer.
[0077] Comparative Example 2
[0078] The only difference between this comparative example and Example 1 is that in step (6), the interface encapsulation layer material (2-mercaptoethanol) is replaced by an equal mass of cyclohexanol.
[0079] The comparison of the normalized absorption intensity test results of the perovskite solar cell provided by Example 1 of the present invention and Comparative Example 1 is shown in the figure below: Figure 2 As shown, it can be seen that compared with the perovskite solar cell of comparative example 1 which does not include an interface encapsulation layer, the light absorption intensity of the perovskite solar cell provided in Example 1 has been improved to a certain extent, which is beneficial to improving the efficiency of the perovskite photovoltaic module.
[0080] The perovskite solar cells provided in Example 1 and Comparative Example 1 were directly placed in water, and the lead concentration in the water was measured by flame atomic absorption spectrophotometry (FAAS). The test results are as follows: Figure 3 As shown, it can be seen that with the increase of time, the lead concentration of the perovskite solar cell without the interface encapsulation layer (Comparative Example 1) increases rapidly. After the interface encapsulation layer is added (Example 1), the lead concentration hardly increases, and the lead leakage is obviously suppressed.
[0081] The perovskite solar cells provided in Example 1 and Comparative Example 1 were placed in an air environment with a relative humidity of 50%, and the photoelectric conversion efficiency ratio of the cells was tested over time. The test results are shown in the figure below: Figure 4 As shown, it can be seen that the efficiency of the solar cell without an interface encapsulation layer (Comparative Example 1) drops to less than 40% of the initial efficiency after 30 days, while the efficiency of the solar cell with an interface encapsulation layer (Example 1) drops by less than 5% after 180 days, which indicates that the safety and stability of the perovskite solar cell are improved after the addition of the interface encapsulation layer.
[0082] The perovskite solar cells provided in the embodiments of the present invention and the comparative examples were stored in an air environment with a relative humidity of 50%. The test results of the photoelectric conversion efficiency (PCE) in the initial state and after storage for a period of time are shown in Table 1.
[0083] Table 1
[0084]
[0085] It can be seen from Table 1 that, compared with the comparative example, the perovskite solar cell provided by the embodiment of the present invention has higher stability in an air environment with a relative humidity of 50%.
[0086] The perovskite solar cells provided in the embodiments of the present invention and the comparative examples were stored in a nitrogen atmosphere, and the test results of the photoelectric conversion efficiency (PCE) in the initial state and after storage for a period of time are shown in Table 2.
[0087] Table 2
[0088]
[0089] It can be seen from Table 2 that, compared with the comparative example, the perovskite solar cell provided by the embodiment of the present invention also has higher stability when stored in nitrogen.
[0090] In summary, the present invention adopts an interface encapsulation strategy in the perovskite photovoltaic module to introduce an encapsulation layer with barrier properties. This layer can not only effectively prevent the migration of ions in the perovskite film and the leakage of lead ions, but also strengthen the bonding between the electrodes by forming an anchoring effect with the top metal electrode (such as silver), thereby significantly enhancing the stability of the entire battery. This method provides an effective solution for improving the safety and long-term reliability of perovskite photovoltaic modules. After the perovskite solar cell was placed in an air environment with a relative humidity of 50% for 180 days, the efficiency of the module obtained by the interface encapsulation strategy did not change by more than 5%. After external encapsulation, the safety and stability of the perovskite photovoltaic module was further improved, which is of great significance for the preparation of safe and stable perovskite photovoltaic modules.
[0091] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the perovskite solar cell and its preparation method and the perovskite photovoltaic module containing the same, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A perovskite solar cell, characterized in that: The perovskite solar cell comprises a conductive substrate, a perovskite layer, an interface encapsulation layer and a metal electrode layer, wherein the interface encapsulation layer is arranged adjacent to the metal electrode layer; The material of the interface encapsulation layer contains functional groups that can form an anchoring effect with the metal electrode, including any one of a thiol group, a phosphine group, an amine group, an amide group or a cyano group, or a combination of at least two of them.
2. The perovskite solar cell according to claim 1, characterized in that The material of the interface encapsulation layer includes any one of 2-mercaptoethanol, tricyclohexylphosphine, triphenylphosphine, dithiothreitol, ethanethiol, ethylenediamine, triethylamine, bis(dibenzylideneacetone)diimine nickel bis(triphenylphosphine), triisopropylphosphine, pentafluorophenyl diphenyl phosphate, tributylphosphine, tricyanomethane, and dicyanomethane, or a combination of at least two thereof; Preferably, the thickness of the interface encapsulation layer is 10-20 nm.
3. The perovskite solar cell according to claim 1 or 2, characterized in that: The perovskite solar cell further includes any one of a hole transport layer, an electron transport layer, and a buffer layer, or a combination of at least two of them.
4. The perovskite solar cell according to any one of claims 1 to 3, characterized in that: The perovskite solar cell comprises a conductive substrate, a hole transport layer, a perovskite layer, an electron transport layer, a buffer layer, an interface encapsulation layer, and a metal electrode layer which are stacked in sequence.
5. The perovskite solar cell according to any one of claims 1 to 4, characterized in that: The conductive substrate includes indium tin oxide conductive film polyethylene naphthalate; Preferably, the material of the metal electrode layer includes any one of aluminum, silver and copper.
6. A method for preparing a perovskite solar cell according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) providing a conductive substrate; (2) forming a hole transport layer on the conductive substrate; (3) forming a perovskite layer on the hole transport layer; (4) forming an electron transport layer on the perovskite layer; (5) forming a buffer layer on the electron transport layer; (6) mixing the material of the interface encapsulation layer and the solvent, stirring to obtain an interface encapsulation layer precursor solution, and coating the interface encapsulation layer precursor solution on the buffer layer by a slit coating method to form an interface encapsulation layer; (7) Forming a metal electrode layer on the interface encapsulation layer to obtain the perovskite solar cell.
7. The preparation method according to claim 6, characterized in that: The solvent in step (6) includes any one of 2,2,2-trifluoroethanol, tetrahydrofuran, and 2,2,2-trifluoroethyl methyl ether, or a combination of at least two thereof.
8. The preparation method according to claim 6 or 7, characterized in that: In step (6), based on 1 mL of the solvent, the amount of the material of the interface encapsulation layer is 0.5-2 mg.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The stirring in step (6) is stirring until the material of the interface encapsulation layer is completely dissolved; Preferably, during the slit coating process in step (6), the gap between the slit coating head and the substrate is controlled to be 50-100 μm, and the speed is controlled to be 8-12 mm / s.
10. A perovskite photovoltaic module, characterized in that: The perovskite photovoltaic module comprises a perovskite solar cell as described in any one of claims 1 to 5; Preferably, the perovskite photovoltaic module is a flexible module.
Citation Information
Patent Citations
A perovskite solar cell with specific structure and a preparation method thereof
CN109216556A
Stable and efficient perovskite solar cell and preparation method thereof
CN112133833A
Enhanced perovskite materials for photovoltaic devices
CN113272312A
Perovskite solar cell with super-hydrophobic packaging layer and preparation method thereof
CN113497189A
Interface modification tin-lead mixed perovskite solar cell and preparation method thereof
CN115020595A